Fabrication, improved performance, and response mechanism of binary Ag–Sb alloy pH electrodes. (20th March 2020) - Liu, Yaosheng; Liu, Hanmeng; Yao, Zhixia; Diao, Yongxing; Hu, Guangxing; Zhang, Qifang; Sun, Yujing; Li, Zhuang
Abstract: pH electrodes exhibited wide applications in the fields of food science, environmental science, and bioanalytical analysis. In this work, we demonstrate the facile fabrication of silver-antimony (Ag–Sb) binary alloy electrodes through a one-step melt casting method. XRD, SEM and EDS were used to characterize the alloy electrodes. The response mechanism of the pH electrode was studied by Tafel plots, which clarified the role of metal (Sb) and metal oxide (SbOads ) in the pH response process. The corrosion resistance of the alloy electrode was researched by electrochemical impedance spectroscopy (EIS), which proved the advantages of the Ag–Sb alloy electrodes. In addition, our Ag–Sb pH electrodes exhibited promising sensing performance with the near-Nernstian response sensitivity is 54.6 mV/pH. The other performances including response time, stability, reversibility, hysteresis, and temperature coefficient, also demonstrated that the Ag–Sb binary alloy electrodes have good pH speciality, and it will potential applications for environmental monitoring in situ. These research results can complement and perfect the theoretical basis of metal/metal oxide pH electrodes, thus guiding the preparation of metal/metal oxide pH electrodes and promoting the exact and extensive application of metal/metal electrodes in more aspects.